2008
DOI: 10.1007/s11172-008-0277-3
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effects in polymolecular nitrogen clusters

Abstract: The structures and stabilities of the van der Waals clusters (N 2 ) n (n = 2-8) have been evaluated using ab initio calculations at the MP2(full)/6 311+G* and CCSD(full)/6 311+G* level of theory. At n = 2-4, the formation of planar and three dimensional structures is possible. At n > 4, only "globular" structures can be formed, whose formation energies increase with the cluster size. As the number of interacting molecules increases, the examined systems exhibit cooperative effects associated with non additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The ab initio study of the (N 2 ) n CO m (n = 1-7; m = 1-3) complexes at the MP2 and CCSD(T) levels of theory with the 6-311+G* basis set showed that the CO-N 2 dimer exists in the form of a series of structurally different but energetically almost equivalent isomers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The ab initio study of the (N 2 ) n CO m (n = 1-7; m = 1-3) complexes at the MP2 and CCSD(T) levels of theory with the 6-311+G* basis set showed that the CO-N 2 dimer exists in the form of a series of structurally different but energetically almost equivalent isomers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Becke−Lee−Yang−Parr three-parameter (B3LYP) functional was employed for exchange and correlation. All the computations were carried out with the 6-311+G(d,p) basis set. ,,,,, Once the fully optimized geometry was obtained, vibration frequency analyses were performed at the same level of theory to characterize the stationary points and to evaluate the zero-point energy correction (ZPE). Topological analyses of the electron density were done based on Bader’s atoms in molecules (AIM) theory by using the AIM2000 program , in order to verify the bond critical points (BCPs).…”
Section: Methodsmentioning
confidence: 99%
“…The reasons may be as follows. The hypercoordinate carbons generally still obey the eight-electron rule. ,,,,, Therefore, the central carbon atom needs only four ligands providing the extra four electrons and the other ligands should give no more electrons to the central carbon. Since boron is electron-deficient, it is possible to attach boron atoms to the saturated central carbon to achieve a higher coordination number.…”
Section: Introductionmentioning
confidence: 99%